Filogenia e biogeografia de uma aranha endêmica da Mata Atlântica brasileira (Araneae: Zoropsidae: Itatiaya) - Márcia de Oliveira Tomasi (2022)
The Brazilian Atlantic Rain Forest (BAF) is one of the most biodiverse regions on the planet, however, the mechanisms that could explain its diversity and species composition are still poorly understood, mostly for invertebrates. The southeastern portion of the BAF stands out for its complex diversification history, in which climatic and geological events are indicated as the main drivers of its diversification. Dated phylogenetic studies of lineages endemic to this region would be important for the investigation of its biogeographic history. The spider genus Itatiaya Mello-Leitão, 1915 (Zoropsidae) is endemic to mountain forests of the southeastern portion of BAF and has a curious distribution pattern, which makes then a suitable model for biogeographic studies in the biome. However, their evolutionary relationships are still to be completely resolved. We used mitochondrial and nuclear markers to test the position of the genus in the family Zoropsidae, elucidate its internal relationships and estimate the divergence times between the eight species of the genus using fossils as calibration points and incorporating an estimated substitution rate for the H3 molecular marker. Additionally, we built a distribution model for Itatiaya to explore the effects of climate and landscape on its current geographic distribution. Our phylogeny recovers Itatiaya within Udubidae. Based on this result and due to the uncertain phylogenetic history of the group, we suggest that its position should be reevaluated through a total evidence analysis. Our dating estimates indicates that the diversification of Itatiaya occurred mostly during the Miocene, suggesting that climatic variations and relief movement in this period may have influenced their speciation events. However, the lack of geographic structuring of the group suggests that the Quaternary glaciations may also have influenced its geographic distribution, enabling secondary contact between populations after speciation. In this study we also describe the male of Itatiaya ywyty Polotow & Brescovit, 2006 for the first time and provide new distribution records of I. modesta Mello-Leitão, 1915; I. pucupucu Polotow & Brescovit, 2006; and I. tubixaba Polotow & Brescovit, 2006.